Assessing the Quality of Life of Parents of Children With Disabilities Using WHOQoL BREF During COVID-19 Pandemic - Ali, Usman; Bharuchi, Vardah; Ali, Nasreen Gulzar; Jafri, Sidra K. (Frontiers in Rehabilitation Sciences, 2021)
Background: Caring for a child with disabilities is a challenging journey, as the parents must meet greater demands when compared with the parents of children without disabilities. Looking after a child with disablities requires additional financial, social, emotional, and physical resources. Coronavirus 2019 (COVID-19) pandemic has made this even more challenging and impacted the quality of life of parents of children with disabilities. Methods: The study was an analytical cross-sectional design with two comparison groups: parents of children with developmental disabilities and parents of children without disabilities. The Urdu version of the WHO Quality of Life Measure Abbreviated version (WHOQOL-BREF) was used to measure the quality of life (QoL) among parents. Sociodemographic data were also obtained from the parents. Results: Parents of children with disabilities had lower overall scores when different domains of QoL were considered (physical health, psychological health, social relationships, and environment) using WHOQoL-BREF. Statistically significant differences were observed in the physical and environmental domains of parental QoL.